PERBEDAAN TINGKAT DEPRESI ANTARA IBU DARI ANAK RETARDASI MENTAL DI SDLB - C DENGAN IBU DARI ANAK NORMAL DI SDN DHUKUHAN KERTEN SURAKARTA - ROSIANA , ROSIANA (2011)
Depression is one of the mental disorders which is often experienced by people between age 15-44. It is recently estimated that female people who experience depression are between 10%-15% and on men are between 5%-12%. It is even estimated that in 2020 depression will take place in the second order of disability cause. People who carry much burden because mental retardation are parents especially mothers. Parents who can't accept the existence of child who suffers mental retardation will experience frustration, feel incapable and lose confidence, this feeling is the one which leads to depression. The purpose of this research is to understand the difference of depression level among mothers of mental retarded child with mothers of normal child. The used research design is analytic descriptive with cross sectional approach. The used measurement tools in this research are L-MMPI "Lie Minessota Multiphasic Personality Inventory" and BDI "Beck Depression Inventory" scale. The total samplings are 50 people who consist 25 mothers of mental retardation child and 25 mothers of normal child. For the hypothesis test, t-test and Mann-Withney test are used. It obtains the value of t-test =2.255 (P=0.030<0.05), therefore H0 is rejected, means that there is a difference of depression level among mothers of child mental retardation in SDLB-C with the mother of normal child in SDN Dhukuhan Kerten Surakarta. That mothers of child mental retardation are more depressed than mothers of normal child. Therefore, the results of this research can provide information about the child's mental retardation and need further research with a more accurate method.